Location-dependent flight cost difference from the lunar surface to an orbital fuel depot and its influence on in situ resource utilisation location selection - Steinert, Sven J.; Zabel, Paul; Quantius, Dominik (Frontiers in Space Technologies, 2024)
Given the increasing relevance of lunar activities, the location selection for in situ resource utilisation (ISRU) facilities is necessary for identifying the most suitable configuration during mission planning. To gather information about the dominant location dependencies, a scenario is established wherein an ISRU product is exported to an orbital depot and its mass costs are used for classification. In the selected scenario, oxygen is produced in an ilmenite reduction plant and subsequently exported to the lunar gateway via an oxygen–hydrogen fuelled launcher operated in a round-trip to refuel oxygen at the lunar surface and hydrogen at the lunar gateway. This showed that the transport cost variations could be avoided entirely or have a recessive influence on the mission’s total costs over an extended period of time, such as 20 years. The identification of the top-10 most optimal locations for various resolutions was altered only slightly upon consideration of flight costs as compared to considering only the ISRU factors; this indicates the insignificance of flight cost dependencies for the analysed case.